Potensi Tanaman Brotowali (Tinospora cordifolia) Sebagai Imunostimulan Pada Udang: Artikel Reviuw - Affandi, Rangga Idris; Muahiddah, Nuri (Universitas Mataram, 2025)
Shrimp is among the most economically important aquaculture species globally, playing a significant role in ensuring both food and economic stability. However, the development of aquaculture, particularly shrimp farming, faces several management challenges, with disease outbreaks being a major concern. One effective strategy for disease control is maintaining shrimp health through preventive measures, such as administering immunostimulants. Natural sources of immunostimulants, especially from plants, are gaining attention. One such plant is guduchi (Tinospora cordifolia), known for its rich array of bioactive compounds. Widely recognized as an ingredient in traditional bitter herbal medicine, guduchi offers various health benefits to humans and holds promise for enhancing shrimp immunity. This literature review aims to highlight the potential of guduchi as an immunostimulant for shrimp. The study applies a systematic literature review approach, involving planning, data collection, analysis, and drawing conclusions. Findings indicate that guduchi contains several compounds capable of boosting the immune response in shrimp, suggesting strong potential for further research and application in aquaculture, particularly in shrimp production